2022
DOI: 10.3389/fimmu.2022.1057932
|View full text |Cite
|
Sign up to set email alerts
|

Immune niches orchestrated by intestinal mesenchymal stromal cells lining the crypt-villus

Abstract: The mammalian intestine is an organ that can be spatially defined by two axes: longitudinal and vertical. Such anatomical structure ensures the maintenance of a relatively immuno-quiescent and proliferation-promoting crypt for intestinal stem cell differentiation while actively warding off the invading intestinal microbes at the villus tip during digestion and nutrient absorption. Such behavior is achieved by the fine coordination among intestinal epithelial cells, intestinal mesenchymal stromal cells and tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…By E14.5, the pseudostratified epithelium undergoes extensive remodeling into a columnar epithelium, which leads to the emergence of a villus structure. To gain insights into the underlying factors that potentially shape fetal gut compartments at this stage, Maimets et al reported that CD29 and PDGFRα + cells are crucial for fetal gut vilification [ 20 , 46 , 68 , 111 , 114 ]. The CD29 + cells expressed high Acta2, Myl4, Des, and LRIG1 levels, which could be the progenitor for fetal gut muscularis mucosa cells.…”
Section: Subepithelial Mesenchymal Stromal Cell Characteristicsmentioning
confidence: 99%
“…By E14.5, the pseudostratified epithelium undergoes extensive remodeling into a columnar epithelium, which leads to the emergence of a villus structure. To gain insights into the underlying factors that potentially shape fetal gut compartments at this stage, Maimets et al reported that CD29 and PDGFRα + cells are crucial for fetal gut vilification [ 20 , 46 , 68 , 111 , 114 ]. The CD29 + cells expressed high Acta2, Myl4, Des, and LRIG1 levels, which could be the progenitor for fetal gut muscularis mucosa cells.…”
Section: Subepithelial Mesenchymal Stromal Cell Characteristicsmentioning
confidence: 99%
“…While these cells could be leukocytes [6], the presence of the IL-36R on fibroblasts has been implied by functional in vitro studies, e.g., [32,35]. Fibroblasts exhibit great heterogeneity in the intestines [36]; thus, to assess the cellular subtype of the mCherry-positive cells, we performed double stained immunofluorescence analyses for the leukocytes and the Il1rl2 reporter (Figure 5). All mCherry-positive cells were also stained for CD45, which identified them as leukocytes.…”
Section: Small Intestine and Colonmentioning
confidence: 99%
“…Hub clusters interacted broadly with other intestinal cell clusters confirming the importance of myeloid, stromal and glial cells as regulators of intestinal homeostasis. [29][30][31][32] When comparing interactions in baseline samples to those obtained 6 months post-SCT the most notable increase occurred between hub clusters 17, 19, and 21 involving epithelial clusters 3 (epithelial stem cell), 4 (enterocyte) and 14 (enterocyte) (Figure 4A). Examination of ligand-receptor pairs revealed signals involving chemokines, extracellular matrix, growth factors and WNT pathway ligands.…”
Section: Sct Restores Homeostatic Macrophages In Refractory CD Patientsmentioning
confidence: 99%